STRUCTURAL EQUATION MODELING OF SUPPLY CHAIN MANAGEMENT, EMPLOYEE INVOLVEMENT, AND EMPLOYEE WORK PERFORMANCE IN THAILAND'S AUTO PARTS INDUSTRY - Apiwat Krommuang; Opal Suwunnamek (My University, 2021)
The objective of this research was to analyse the structural equation modelling (SEM) of supply chain management, employee involvement, and employee work performance in Thailand's auto parts industry. The sample group included 383 employees operating in the aforementioned industry using SEM processing by the AMOS program as the tool. From the research, the latent variable of supply chain management had a direct positive influence on the latency of employee involvement and employee work performance with statistical significance. Simultaneously, the latency of employee involvement had no direct positive influence on the latency of employee work performance. Therefore, the latency of supply chain management did not indirectly influence the latency of employee work performance through the latency of employee involvement.
Keywords: Quality and Supply Management